Urban–rural difference in factors associated with childhood functional difficulty in Bangladesh: a cross-sectional study - Yesmin, Mst Farjana; Chowdhury, Mohammad Rocky Khan; Bornee, Farzana Akhter; Kader, Manzur; Mondal, Md Nazrul Islam; Hossain, Mohammad; Rashid, Mamunur (Frontiers in Public Health, 2023)
Objective Early childhood functional difficulty poses a substantial worldwide public health challenge, leading to adverse effects on children's quality of life and overall productivity. Moreover, it represents a significant social and economic problem in Bangladesh. Therefore, the current study aimed to identify factors contributing to childhood functional difficulty in Bangladesh within the context of urban-rural areas.Methods A nationally representative cross-sectional survey data from Multiple Indicator Cluster Survey (MICS), 2019 in Bangladesh was used in this study. Chi-square test and multivariable logistic regression analyses were carried out to identify factors associated with childhood functional difficulty.Results Functional difficulties were found in approximately 3.3% of children 2-4 years of age in urban areas and 2.5% in rural areas. Having a mother with functional difficulties and undernutrition were identified as significant factors common in both urban and rural areas. Further, mothers who had no formal education (AOR=2.76, 95%CI=1.18-6.45) and experienced infant death (AOR=1.94, 95%CI=1.01-3.70) were identified as significant factors of functional difficulty in urban areas. On the other hand, in rural areas, no access to mass media, children with acute respiratory infection (ARI) (AOR=2.13, 95%CI= 1.39-3.28), female sex (AOR= 0.69, 95%CI=0.53-0.91), child undernutrition (AOR=1.73, 95%CI=1.32-2.27) and poorer socio-economic status (AOR=1.95, 95%CI=1.08-3.55) were found significant factors.Functional difficulty was found to be present in one out of every 35 children age 2 to 4 years in Bangladesh. Childhood functional difficulties were reported slightly higher in urban areas as compared to rural areas. Reducing childhood difficulties in urban areas demands comprehensive strategies: quality healthcare, inclusive education, community support, better information systems, and collaboration. To achieve urban-rural parity in child health, address disparities in economic development, healthcare, and education, especially for girls.